Artificial Intelligence in Education Management: A Bibliometric Mapping of the Intellectual Structure and Emerging Research Themes - Winalda Adelia (Har Press Indonesia, 2025)
This study explores the intellectual structure and emerging research trends of artificial intelligence in education management. It identifies six major research streams: (1) ai-driven educational governance, data-centric decision making, and digital transformation, (2) machine learning-based decision support systems and predictive analytics in education management, (3) data-driven educational intelligence and learning analytics in higher education, (4) ai-enabled educational leadership and sustainable development, (5) institutional effectiveness and ai-supported management systems, and (6) foundational education management as the core conceptual domain. co-word analysis further reveals emerging thematic patterns such as artificial intelligence applications, decision-making systems, machine learning, learning analytics, digital transformation, and information management in educational contexts. in terms of methodology, this study employs a bibliometric approach using data from 91 journal articles indexed in Scopus, applying bibliographic coupling and co-word analysis to examine the structure, evolution, and thematic development of the field. the bibliographic coupling analysis identifies the current intellectual structure of the research domain, while co-word analysis uncovers its conceptual evolution and emerging research directions. the findings confirm that artificial intelligence is a key driver in transforming education management systems into more intelligent, data-driven, and adaptive frameworks. the study contributes to theoretical development in educational management and socio-technical systems by positioning ai as a central enabler of institutional transformation. this research also provides practical insights for policymakers, educational leaders, and administrators in designing effective ai-based decision support and governance systems to enhance educational performance and institutional sustainability.